Perjanjian Kredit pada Bank Perkreditan Rakyat - Ashadi L Diab (Al-'Adl, 2017)
An agreement is a legal relation of property between two parties, while the other party has the right to demand its implementation. In order for the agreement to have the force of law, it must meet the requirements of the validity of the agreement contained in article 1320 of the Civil Code. One of the most important things in the credit agreement of the bank is the guarantee for the lending party or the bank (Creditor) guarantee in relation to the credit is one of the conditions for the grant of credit application. The guarantee here is not only the property of the debtor, but also can be an immaterial guarantee. In forming credit there needs to be a guarantee, so there is certainty that the credit given to the debtor can be accepted again in accordance with the conditions that have been determined. Guarantee commonly used by BPR "Latunru Latinro" Makassar is a guarantee in the form of Fidusia that is motor vehicle, car also the right of dependents in the form of land by using notary deed. In solving the problem loans BPR "Latunru Latinro" Makassar as far as possible avoid the settlement through legal channels and seek settlement in a familial way.